12th International Symposium on Sound and Vision Engineering and Mastering - Bożena Kostek (Archives of Acoustics, 2014)
Sound engineering is an interdisciplinary and rapidly expanding domain. It covers many aspects, including sound mastering technology, music information retrieval providing a part of multimedia applications, sound perception, electroacoustics, sound synthesis, sound restoration and also medical applications. These topics have been covered by presenters during the 12th International Symposium on Sound and Vision Engineering and Mastering (ISSVEM'07), which was organized by the Multimedia Systems Department of the Gdańsk University of Technology on June 15-16, 2007. The Symposium was held under the auspices of the Polish Section of the Audio Engineering Society and the Polish Academy of Sciences and provided a valuable forum for the knowledge exchange based on diverse experiences and a wide range of technical and music expertise. Outcomes of this Symposium included extended versions of papers, which are all application-oriented and state-of-the-art, trying to identify current trends and practice in sound engineering domain. All the articles submitted to this issue were chosen for publication after two additional reviewers' opinions according to the peer review standard. We hope that these papers will be interested to specialists from many areas.